(3NRGfI GdCOH hZGjI GdCQHs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s ((3jhSa Hf MSf Hf jhfS s)
(3ChdgG (B:s
(3hHYO agPg GdHOjYI GdJi fSLJgG HeOMg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Sei JPcGQ hbO GfJgJ GdZGjI HMeO Gddg Edi MSf GdNJGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B426s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs